Chapter 6: Our time - Heiskala, Risto (Will Europe Work?, 2001)
The article focuses on Europe in the age of global networks and flowing identities. In the article the author discusses the articulation of Europe. He starts with a discussion on the identity of Europe, goes on with a discussion of globalization and closes with an attempt to tie these two themes together. He then raises, in a new context, sociologist Karl Polanyi's question: "What Kind of a Time Is Our Time?" Throughout the article, specific emphasis is put on the European Union, as this network state currently uniting fifteen and in the nearest future possibly twice as many European states as today is often what is referred to combined with the term "Europe", even if it would be a mistake to believe that these two are identical. The article also throws light on the affect of Islam on the countries of Europe. In several European countries there are enclaves of millions of Muslim migrant workers and there are Muslim countries at the borders of Europe in North Africa and the Middle East.
Keywords: Europe; Islam; globalization; identity (philosophical concept); immigrants

Karl Polanyi and the creation of the "market society" - Gootenberg, Paul (The other mirror : grand theory through the lens of Latin America (Edited by Centeno, Miguel Angel, López-Alves, Fernando)., 2001)
Keywords: Latin America; economic history; philosophy; politics and government; social sceinces

Karl Polanyi's Great Transformation and the Current Transformations in Central Europe - Hake, Eric R.; Neale, Walter C. (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Keywords: agriculture; collectives; communes; comparison of public and private enterprises and nonprofit institutions; contracting out; economic thought; history of economic thought: individuals; illegal behavior; legal institutions; nonprofit institutions; privatization; public enterprises; socialist systems and transitional economies: legal institutions; transitional economies

Contesting the "Great transformation" : local struggles with the market in South India - Herring, Ronald (Agrarian studies : synthetic work at the cutting edge, ed. by James C. Scott and Nina Bhatt, 2001)
Keywords: India; agrarian studies

Groundwork for an Institutional Economic Approach to 'Transition': Smith and Polanyi Reconsidered - Ozveren, Eyup (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Keywords: Marxist; SMITH, Adam, 1723-1790; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought through 1925: socialist; history of economic thought: classical; history of economic thought: individuals; socialist systems and transitional economies: performance and prospects P27

What Karl Polanyi Found in Dahomey - Sandall, Roger (The culture cult : designer tribalism and other essays, 2001)
A study of the social effects of romantic primitivism.
Keywords: alternative lifestyles; culture; meningen; modern civilization - public opinion; primitive societies - public opinion; primitivism